Penatalaksanaan Laki-Laki Usia 20 Tahun Dengan Skabies Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Tanjung Sari Natar - Khairunnisa, Salma; Angraini, Dian Isti (Medula, 2025)
Scabies is a skin disease caused by infestation and sensitization with the parasite Sarcoptes scabiei var. hominis. Other names or synonyms of scabies are "agogo itching", "gudig", and "budukan". The prevalence of scabies in the world reaches 300 million people every year. Many variables contribute to the development of this disease, such as low socioeconomic status, inadequate personal hygiene, age, level of knowledge, and direct or indirect interactions with sufferers. Scabies is often ignored because it is not life threatening, even though this disease can become chronic and cause complications, as well as reducing the sufferer's quality of life. Therefore, appropriate holistic treatment is needed using a family medicine approach to achieve therapeutic success. This Study aims to apply the principles of a holistic and comprehensive family doctor approach in detecting internal and external risk factors and resolving problems based on EBM (Evidence Based Medicine) which is family approach and patient centered. This study is a case report. The data obtained were primary data obtained through alloanamnesis, physical examination, and home visits, and secondary data obtained from the patient's medical records. An. 20 years old HY came with complaints of itching on his right leg since more than a week ago and there were small pimples the size of pins filled with clear fluid in the itchy area which he then scratched and broke and became blackish scabs. The patient is worried that the complaint will get worse and interfere with the patient's activities. Next, holistic management is carried out, namely intervention using poster media. In the evaluation, results were obtained in the form of of a better understanding of the disease and changes in behavior that had an impact on the success of therapy. After carrying out holistic and comprehensive management, the patient experienced an increase in knowledge about the disease by 3.75 points. Complaints of itching and rashes on the skin have decreased and patients have improved personal and environmental hygiene.